Power-efficient and solution-processed red phosphorescent organic light-emitting diodes by choosing combinations of small molecular materials to form a well-dispersed exciplex co-host. Issue 16 (3rd April 2018) - Yao, Bing; Lin, Xingdong; Zhang, Baohua; Wang, Hailong; Liu, Xuejing; Xie, Zhiyuan
Abstract : Intrinsic compatibility of exciplex couple determines the EL performance of the resultant solution-processed phosphorescent OLEDs, particularly driving voltage behaviours. Abstract : Exciplexes consisting of a combination of hole-transporting and electron-transporting materials and exhibiting narrow HOMO–LUMO gaps and bipolar transport ability are promising host choices in solution-processed phosphorescent organic light-emitting diodes (s-PhOLEDs). However, till date, there have been just a few reports on power-efficient s-PhOLEDs that use such an exciplex host structure. Herein, we successfully fabricated ultralow driving-voltage and power-efficient red s-PhOLEDs with a common hole-transporting and electron-transporting material combination, i.e. m -MTDATA:OXD-7 as exciplex co-host and Ir(MDQ)2 acac as red dopant. The resultant s-PhOLEDs achieve satisfactory overall electroluminescent (EL) performance, i.e., light turn-on voltage at 2.4 V, maximum luminance of 26 385 cd m −2, peak external quantum efficiency (EQE) of 15.5% and peak power efficiency (PE) of 36.9 lm W −1, respectively. However, a s-PhOLED using an exciplex-forming co-host couple of m -MTDATA:TmPyPB displays high turn-on voltage of 4.4 V and low EQE and PE of 9.4% and 10.1 lm W −1, respectively. The mechanism accounting for such an EL difference of s-PhOLEDs using m -MTDATA:OXD-7 or m -MTDATA:TmPyPB exciplex host were explored. It is found that the intrinsic incompatibility between m -MTDATA and TmPyPB does play a key role, which significantly deteriorates the bipolar charge transport capability of the solution-processed exciplex co-host matrix and consequently the EL performance of the resultant s-PhOLEDs.